Low carbon economic dispatch of power system at multiple time scales considering GRU wind power forecasting and integrated carbon capture - Can Ding; Yiyuan Zhou; Guang Pu; Hongrong Zhang (Frontiers in Energy Research, 2022)
To achieve carbon neutrality in electricity, measures such as increasing the share of renewable energy sources such as wind power and achieving more accurate and faster wind power forecasting, and low carbon retrofitting of thermal power units are all important to achieve the goal. Firstly, the GRU prediction algorithm was used to forecast wind power, which performed well in terms of prediction accuracy and model training speed. Then, we continue to fully utilize the source-side low-carbon characteristics by installing flue gas bypass systems and liquid storage in carbon capture plants to form an integrated carbon capture plant operation, thereby reducing carbon emissions and the proportion of abandoned wind. Secondly, a three-stage low carbon economic dispatch model is established to reduce wind abandonment by combining wind power forecasts on different time scales. Finally, a case study was carried out using a modified IEEE-39 node system. The results show that the proposed three-stage integrated dispatching method can make full use of wind energy and achieve the goal of economic dispatching of the power system.